Bi-objective covering salesman problem with uncertainty - Tripathy, Siba Prasada (Journal of Decision Analytics and Intelligent Computing, 2023)
Humanitarian relief transportation and mass fatality management activities are the most strenuous tasks after a natural or artificial disaster. A feasible and realistic transport model is essential for accomplishing the tasks in a planned way. Covering Salesman Problem (CSP) is a variant of Traveling Salesman Problem (TSP) which has been used in many application areas, including disaster management. In this paper, we consider a bi-objective CSP in an uncertain environment where Interval Type 2 fuzzy numbers represent the costs of the edges. A new local search technique is introduced in the memetic algorithm, which has been used to solve the problem. A computational experiment on a set of instances indicates the effectiveness of the introduced local search technique along with the proposed methodology.